Extracellular Vesicles From Women With Severe Preeclampsia Impair Vascular Endothelial Function. Issue 4 (21st December 2022) - Murugesan, S.; Hussey, H.; Saravanakumar, L.; Sinkey, R.; Sturdivant, A.; Powell, M.; Berkowitz, D.
Abstract : ( Anesth Analg . 2022;134:713–723) Preeclampsia causes worldwide maternal and neonatal morbidity and mortality. Previous studies confirm the placenta is heavily related to preeclampsia and vascular dysfunction likely caused by pro-angiogenic and anti-angiogenic factors due to changes in uteroplacental blood flow and oxygenation from abnormal trophoblastic invasion of the uterine spiral arterioles. A previous study involving a mouse model supports the idea of extracellular vesicles (EVs), particles which interact with microRNA and impact endocrine or paracrine organs, from the placenta being a main culprit for triggering preeclampsia. All pregnancies show levels of placenta-derived EVs (pEVs), but those with preeclampsia show an increased level, impacting the growth and weight gain of the child, levels of endothelial nitric oxide synthase (eNOS) to endothelial cells leading to irregular embryo development, implantation, trophoblast invasion, placental vascular development, function, and increased level of endothelial dysfunction. This study primarily measures the effect of EVs from both severe preeclampsia and normotensive patients on human aortic endothelial cells to test the hypothesis that preeclamptic EV cargo impairs endothelial function and regulation of NO signaling.